Thar Prabha: A new high-yielding wood apple variety for dryland - Yadav, Vikas; Singh, A K; Hiwale, S S; Singh, Sanjay; Sharma, B D (Indian Horticulture, 2023)
The wood apple tree (Feronia limoni L.) is an underutilized fruit crop which is locally known as elephant apple, monkey fruit, curd fruit, kata and kaithbel in different part of the country. It belongs to citrus family Rutaceae. It is native to south India and grows naturally in scattered manner in dry land and forest area in all parts of the country excluding high altitude and in cold region. It prefers dry hot condition at flowering and fruit setting stage. The tree is tolerant to both drought and waterlogging condition. The mature fruit have creamy-brownish, sticky, resinous, astringent, acidic-sweet pulp. The fruit pulp has pleasant aroma and seed scattered throughout fruit. The fruit and plant parts (leaf, stem, bark, fruit and seed) have good medicinal and curative values.